Unravelling material/digital shopping space: An assemblage approach. Issue 11 (24th August 2020) - Rao, Fujie
Abstract: In this paper, I propose a new retail typology to explore emerging shopping space through the lens of assemblage thinking. The recent rise of online retailing has stimulated substantial net‐closures of brick‐and‐mortar shops—what some call the "retail apocalypse". While being widely covered by the news media, the impact of online retailing on shopping space receives little attention in existing research. There is, in particular, a lack of a retail typology that regards online retailing as a form of shopping space. The current four primary typologies of scale, retail offer, control, and morphology are biased towards material shopping centres (agglomeration of shops). In an attempt to tackle this issue, I introduce Deleuzian assemblage theory. Assemblage prioritises interrelation, transformation, and difference, and suggests that both the virtual and actual are real and they can morph into a whole. In light of assemblage, I redefine a retail type as a "diagram" depicting how some shopping spaces work in general while still being geared to the particularity of each instance, and I focus on the "interface" between people and shops. This diagrammatic typology of interface could thus be adapted to emergent and diversified material, digital, and material/digital shopping spaces.